A Correlational Study on Teachers’ Level of Competence on and Attitudes Towards ICT Integration: Basis for the Development of Extension Training Program - Beltran, Hazel (International Journal of Humanities and Education Development (IJHED), 2022)
The integration of ICT in teaching and learning processes brings about powerful learning environments with the recent shift in Blended Learning-Online Distance Learning and helps teachers to deal with knowledge in active, self-directed and constructive ways. The purpose of this study was to determine if the adapted theory of Reasoned Actions as presented by Ajzen and Fishbein (1980) and Technological Acceptance Model developed by Davis (1989) relates to teachers’ competence on and attitudes in the implementation of ICT to justify the interim guidelines on the across implementation of BL-ODL and MDL modalities by BE-Learning Continuity Plan of Department of Education as per memorandum of LDM1 and LDM2 in the current school year. As part of a pilot-testing program of the LGU, the researcher sought to develop an instrument that would effectively measure the teachers’ level of competence on and attitudes with the utilization of ICT. Two schools JHS and SHS were studied since they belong to the same cluster. The study included 25 teacher-respondents from KERISHS-SHS and 25 teacher-respondents from GABHS-FBSHS. Each respondent completed the survey questionnaire, and gathered the necessary data for each level of competence on and attitudes that could benefit the entire educational community. The researcher applied Pearson’s r correlation in order to determine if a significant correlation existed. The results of the study revealed to have a significant or strongly positive relationship data to support the study. This research may encourage administrators to recognize and utilize the availability of ICT computer-assisted laboratories and enhance the scope of internet connection in formal and informal learning environments available in the school district